2019
DOI: 10.1186/s13046-019-1114-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: A positive feedback loop consisting of C12orf59/NF-κB/CDH11 promotes gastric cancer invasion and metastasis

Abstract: Background Metastasis remains the main cause of cancer-related death for gastric cancer (GC) patients, but the mechanisms are poorly understood. Using The Cancer Genome Atlas (TCGA) data base and bioinformatics analyses, we identified C12orf59 might act as a potential oncogenic protein in GC. Methods We investigate the expression pattern and clinical significance of C12orf59 in two independent cohorts of GC samples. In the training cohort, we used the X-tile program sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Consistent with our results, it has been recently reported that the downregulation of TMEM52B correlated with poor survival of renal cell carcinoma patients [ 10 ]. In contrast, TMEM52B is also associated with poor survival of gastric cancer patients, and reported to promote gastric cancer cell invasiveness and metastatic capacity [ 30 ]. Whether TMEM52B exerts positive or negative influences by cancer type or in a context-dependent manner needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, it has been recently reported that the downregulation of TMEM52B correlated with poor survival of renal cell carcinoma patients [ 10 ]. In contrast, TMEM52B is also associated with poor survival of gastric cancer patients, and reported to promote gastric cancer cell invasiveness and metastatic capacity [ 30 ]. Whether TMEM52B exerts positive or negative influences by cancer type or in a context-dependent manner needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…One of its basic functions is to mediate cell-cell and cell-matrix junctions, thus regulating cell movement and the epithelial-mesenchymal transition (32,33). In addition to its involvement in cell movement, CDH11 is a positive regulator of NF-κB signaling (34). Upregulated CDH11 in GC increases NF-κB activity and promotes the nuclear localization of NF-κB p65, leading to cell invasion and metastasis.…”
Section: Univariate Analysismentioning
confidence: 99%
“…15 Recently, it has been observed to be deregulated and play crucial roles in a variety of cancers. [16][17][18][19][20] Despite accumulating research on its involvement in carcinogenesis and cancer management, this is the first study to identify the associations of miR-654-5p with RA response to TGT treatment. In the current study, our microarray data based on the discover cohort and independent test data based on the large validation cohort both verified the significant upregulation of miR-654-5p in peripheral blood of TGT-responders compared to nonresponders, in coincided with the findings based on CIA mice.…”
Section: Discussionmentioning
confidence: 99%